Financial Distress As a Mediator Between Capital Structure, Earnings Management, and Tax Aggressiveness - Wardhana, Rony; Anam, Saiful; Nur Lailiyatul Inayah; Teodora Winda Mulia; Roy Budiharjo; Heru Tjaraka (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
Purpose: This study explores how capital structure, earnings management, and financial distress influence tax aggressiveness among manufacturing firms on the Indonesia Stock Exchange. Amid increasing tax regulations and levies, this research provides critical insights. Methodology/Approach: Using a quantitative explanatory research approach, the study analyses secondary data from financial statements of 41 purposively sampled manufacturing firms. Findings: Capital structure significantly impacts financial distress and tax aggressiveness, whereas earnings management does not significantly impact either variable. Interestingly, financial distress mediates the relationship between capital structure and tax aggressiveness, but does not mediate the relationship between earnings management and tax aggressiveness. Lastly, financial distress has a significant positive effect on tax aggressiveness. Practical Implications: Findings help firms optimise financial strategies and assist regulators in curbing aggressive tax practices. Originality/Value: This study underscores financial distress as a crucial mediator in corporate tax strategies within the manufacturing sector.